Characteristics of sediments from Amvrakikos Gulf, Greece - Naeher, Sebastian; Geraga, Maria; Papatheodorou, George; Ferentinos, George; Kaberi, Helen; Schubert, Carsten J (Supplement to: Naeher, S et al. (2012): Environmental variations in a semi-enclosed embayment (Amvrakikos Gulf, Greece) - reconstructions based on benthic foraminifera abundance and lipid biomarker pattern. Biogeosciences, 9(12), 5081-5094, https://doi.org/10.5194/bg-9-5081-2012, 2012)
The evolution of environmental changes during the last decades and the impact on the living biomass in the western part of Amvrakikos Gulf was investigated using abundances and species distributions of benthic foraminifera and lipid biomarker concentrations. These proxies indicated that the gulf has markedly changed due to eutrophication. Eutrophication has led to a higher productivity, a higher bacterial biomass, shifts towards opportunistic and tolerant benthic foraminifera species (e.g. Bulimina elongata, Nonionella turgida, Textularia agglutinans, Ammonia tepida) and a lower benthic species density. Close to the Preveza Strait (connection between the gulf and the Ionian Sea), the benthic assemblages were more diversified under more oxygenated conditions. Sea grass meadows largely contributed to the organic matter at this sampling site. The occurrence of isorenieratane, chlorobactane and lycopane supported by oxygen monitoring data indicated that anoxic (and partly euxinic) conditions prevailed seasonally throughout the western part of the gulf with more severe oxygen depletion towards the east. Increased surface water temperatures have led to a higher stratification, which reduced oxygen resupply to bottom waters. Altogether, these developments led to mass mortality events and ecosystem decline in Amvrakikos Gulf.